Executable Images: The Enactment and Distribution of Movies in Computer Networks. - Gonring, Gabriel Menotti (Velvet Light Trap: A Critical Journal of Film & Television)
The article discusses the impact of the digitalization of media on cinema studies, arguing that computer-based motion pictures (movies) are executable software. Topics include the history of computing, the principles of computer operation, and the mediatic visual qualities of user interfaces. The video advertisement "And Then There Was Salsa" on the online video-hosting platform Vimeo is analyzed. The nature of peer-to-peer (p2p) network file sharing is considered. The author claims that digital objects are inherently fragile.